PER VAGINAL DELIVERY OF A FETUS FOLLOWING PARTIAL DETORSION IN A BUFFALO - SATHIAMOORTHY, T; RAJA, S; THIRUMURUGAN, K; THIRUNAVUKKARASU, P; BALASUBRAMANIAN, S; ASOKAN, S A (The Indian Journal of Animal Reproduction, 2023)
Successful per vagina! delivery of a fetus following partial detorsion in a buffalo is presented.
Keywords: Partial detorsion; Per vaginal delivery; Buffalo